(untitled) (gjstudies, 2025)
This research investigates the underexplored intersection between auditor tenurelength and financial reporting objectivity through a novel computational lens, departing from traditional econometric approaches that dominate the auditing literature.We introduce a hybrid methodology combining agent-based modeling with naturallanguage processing techniques to simulate auditor-client interactions over extendedtenure periods, capturing nuanced behavioral dynamics that quantitative financial metrics alone cannot reveal. Our model incorporates three distinct agent types—auditors,client management, and audit committee members—each programmed with adaptivelearning algorithms that evolve their decision-making patterns based on accumulatedinteraction history, reputational concerns, and perceived relationship costs. We analyze how objectivity erosion manifests not merely through discretionary accrualsbut through subtle shifts in audit documentation language, argumentation patternsin contentious accounting judgments, and the gradual convergence of risk assessmentframeworks between auditor and client. The simulation spans virtual tenure periodsequivalent to 20 years, tracking 500 unique auditor-client dyads across diverse industryenvironments and regulatory regimes. Results reveal a non-linear relationship betweentenure length and objectivity erosion, with critical inflection points occurring at years7-8 and 14-15, challenging the conventional binary view of tenure effects. Furthermore, we identify specific linguistic markers in audit documentation that serve as earlywarning indicators of objectivity compromise, detectable through our specialized NLPalgorithms before material financial misstatements occur. These findings contributeoriginal insights to the auditor independence literature by demonstrating that objectivity erosion follows complex temporal patterns influenced by relational capital accumulation, cognitive entrenchment, and adaptive normalization of client practices. Ourcomputational approach offers a novel paradigm for auditing research, enabling thestudy of longitudinal phenomena through controlled simulation of social and cognitiveprocesses that are otherwise inaccessible to empirical observation